Jihad Menurut Pola Pikir Syekh Muhammad Abu Bakar Syatha Dalam Kitab I’anatut Thalibin (Perang Bukan Tujuan Utama) - Ishom Fuad, Muhammad (JURNAL PUSAKA: Media Kajian dan Pemikiran Islam, 2024)
This research is motivated by the existence of a misunderstanding among the public regarding the meaning of jihad. In general, when the word "jihad" is mentioned, some people immediately associate it with violence, war, even suicide bombings. This assumption was also the background to the terrorist attacks on the World Trade Center (WTC) and the Pentagon on September 11 2001. The change in the meaning of jihad, which should have broad dimensions and not only be limited to physical aspects, has damaged the image of the Islamic religion as a whole. Sheikh Abu Bakar Muhammad Syatha in his book, I'anatut Thalibin, states that jihad is carried out to create prosperity and prosperity for all mankind. In this context, jihad is more related to efforts to create prosperity and happiness in life for Muslims without war or bloodshed. This research aims to determine the application of jihad without violence or war according to the mindset of Sheikh Abu Bakar Muhammad Syatha. The research method used is qualitative research with a library research approach, collecting data and information from various books. Data collection techniques involve searching the literature as primary and secondary sources. The results of the research show that, according to the mindset of Sheikh Abu Bakar Muhammad Syatha, jihad is an effort to create prosperity and prosperity for Muslims, therefore when prosperity and prosperity can be created without war, war should be avoided because war is a medium, not the main goal.